Back Cover: Experimental and Theoretical Study of the Reactivity of Gold Nanoparticles Towards Benzimidazole‐2‐ylidene Ligands (Chem. Eur. J. 30/2016). Issue 30 (15th June 2016) - Rodríguez‐Castillo, María; Lugo‐Preciado, Gustavo; Laurencin, Danielle; Tielens, Frederik; van der Lee, Arie; Clément, Sébastien; Guari, Yannick; López‐de‐Luzuriaga, José M.; Monge, Miguel; Remacle, Françoise; Richeter, Sébastien
Abstract : The calculated Au38 cluster is represented in the middle of the cover picture, coated by the N‐heterocyclic carbenes (NHCs) presented in the paper. The falling binary code "01" illustrates that the Au38 clusters are issued from DFT calculations. Molecular bis(NHC) gold complexes obtained from the functionalization of the particles are represented around the cluster. An experimental 1 H NMR solid‐state spectrum is shown in the lower part of the cover to remind the reader that the study combines experimental and computational approaches. More information can be found in the Full Paper by F. Tielens, F. Remacle, S. Richeter et al. on page 10446 ff.